Teachers' professional vision: exploring and clarifying the concept - Tomáš Janík; Eva Minaříková (Czech Pedagogical Society, 2012)
This theoretical study introduces the concept of professional vision into Czech academic discourse as one of the potential concepts that can be used when contemplating (teacher) professionalization. At the beginning the authors mention selected attempts to define characteristics of a profession and introduce their view of the issue of teacher professionality that is built on three dimensions - professional vision, professional knowledge and professional action. They further suggest the relationships among these dimensions in the model of pedagogical reasoning and action (Shulman, 1986) and the ALACT model of reflection (Korthagen, 2011).Professional vision in general and specifically in the teaching profession is discussedand its existing conceptualizations are described. Based on other theoretical and empirical studies connected to this issue, the authors then suggest their own approach to teachers' professional vision. The relationship between professional vision and reflection on the spiral of pedagogical reasoning and action is elaborated on. In the end,the usability of the concept of professional vision in teacher education is discussed, specifically in the process of development of an e-learning (video)environment for(prospective) teachers.